Information and Communications Technology in Land Administration Projects - Stanley, Victoria; Cook, Edward; Tarhanen, Mika; Adlington, Gavin; Bell, Keith (World Bank, Washington, DC, 2012)
Application of Information and Communications Technology (ICT) to land related projects is now a widespread phenomenon, through both donor-supported interventions and autonomous development. Since the mid-1990s the World Bank has been increasingly involved in ICT land project implementations. The advantages have proven substantial in reducing the time required to complete transactions, improving access to information by the public, as well as other government agencies, reducing the costs of data acquisition, and contributing to standardization of system design. The successful application of ICT to land projects has increased since the 1990s, as lessons from the first tier of programs became clear and were subsequently applied. This note summarizes the demonstrated advantages of ICT application, as well as the key lessons learned. Data acquisition is more feasible and costs less by applying ICT than often-used technology that is quite sophisticated. The use of high, but robust, technology for data acquisition (satellite imagery, digital orthophotos, CORS, GPS) provides more simplification, increased efficiency, less cost, and greater accuracy.